2016
DOI: 10.1016/j.jpeds.2016.08.078
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Scabies in a 5-Year-Old Child

Abstract: A 5-year-old child presented with a 1-month history of nocturnal and generalized pruritus and multiple tense bullae over both hands. No family members were affected with similar signs or symptoms. Physical examination revealed multiple tense blisters, 0.5-1.2 cm in size, containing clear fluid on both palms (Figure 1). Nikolsky sign was negative. Burrows, erythematous papules, and excoriations on the web spaces of fingers were noted (Figure 2; available at www.jpeds.com). With the clinical diagnosis of bullous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“… 8 27 Including the patient in this report, bullous scabies has been described in 46 individuals: 31 men (69% of patients) and 14 women (31% of patients). 8 , 25 The gender was not described in one child. 25 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 8 27 Including the patient in this report, bullous scabies has been described in 46 individuals: 31 men (69% of patients) and 14 women (31% of patients). 8 , 25 The gender was not described in one child. 25 …”
Section: Discussionmentioning
confidence: 96%
“…Nearly two-thirds of the individuals who presented with bullous scabies (29 of 46 patients, 63%) were older than 60 years; only 17% of the individuals (8 of 46 patients) were less than 30 years. 9 , 13 , 16 , 22 , 25 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnoses of tense palmar bulla in children include infantile bullous pemphigoid, epidermolysis bullosa or bullous scabies 4,5 . As in our case, Gram‐staining of the bulla aspirate may be useful in the diagnosis of bullous impetigo with atypical presentations.…”
Section: Answermentioning
confidence: 57%
“…The previous review demonstrated that BS commonly afflicts the elderly with a median age of 70 years with a male predilection, 1 and only four were younger than 10 years. [2][3][4][5] However, Boralevi et al 6 reported that 6.2% patients of scabies (12 out of 193) below 15 years presented blisters, implying that BS might not be so rare in children. Interestingly, the present two cases were boys with of age 7 years as well as 6 months and were diagnosed by our groups within only 2 years, suggesting that BS in children may be more common than our anticipation indeed.…”
Section: Discussionmentioning
confidence: 99%
“…3 Among them, only four were found to be below than 10 years. [2][3][4][5] Herein, we added another two cases with this rare condition who were younger than 10 years.…”
Section: Introductionmentioning
confidence: 99%